"The Role of Sustainable Urban Planning in Libya to Enhance Climate Change Adaptation" (Comprehensive Journal of Science, 2026)
Libyan cities, including Tripoli, Benghazi, and Sabha, have undergone significant urban transformations due to rapid population growth and unplanned urban expansion, which have increased pressure on infrastructure and natural resources. The study reveals that previous urban planning efforts largely overlooked climate change considerations, increasing cities’ vulnerability to hazards such as heat waves, floods, desertification, and groundwater depletion.The findings highlight the critical role of sustainable urban planning as a strategic tool to mitigate these risks through resilient and environmentally friendly infrastructure, sustainable resource management, control of unplanned urban sprawl, and enhanced community and private sector participation in planning and implementation.The research concludes that integrating climate change considerations into sustainable urban planning enhances cities’ resilience and adaptive capacity, promoting balanced and sustainable urban development that safeguards both residents and the environment while reducing the negative impacts of climate change on Libyan cities.